2022
DOI: 10.3390/foods11193077
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Properties of Raw Milk throughout the Year and Their Relationships to Quality Parameters

Abstract: Raw milk microbiota is complex and influenced by many factors that facilitate the introduction of undesirable microorganisms. Milk microbiota is closely related to the safety and quality of dairy products, and it is therefore critical to characterize the variation in the microbial composition of raw milk. In this cross-sectional study, the variation in raw milk microbiota throughout the year (n = 142) from three farms in China was analyzed using 16S rRNA amplicon sequencing, including α and β diversity, microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…appears in raw milk every season, which indicates that it is a bacterium, and that its thermostable alkaline proteases may play an important role in raw milk spoilage ( Jonghe et al, 2011 ; Li et al, 2019 ). A previous study analyzed the microbial diversity of year-round raw milk from three pastures in the Hebei province by using high-throughput sequencing, detected the bacteria responsible for contaminating raw milk at different times, and investigated the correlation between these bacteria and raw milk quality parameters ( Yuan et al, 2022 ). The results showed that psychrophilic bacteria in all three pastures were a serious threat to the quality of raw milk.…”
Section: Discussionmentioning
confidence: 99%
“…appears in raw milk every season, which indicates that it is a bacterium, and that its thermostable alkaline proteases may play an important role in raw milk spoilage ( Jonghe et al, 2011 ; Li et al, 2019 ). A previous study analyzed the microbial diversity of year-round raw milk from three pastures in the Hebei province by using high-throughput sequencing, detected the bacteria responsible for contaminating raw milk at different times, and investigated the correlation between these bacteria and raw milk quality parameters ( Yuan et al, 2022 ). The results showed that psychrophilic bacteria in all three pastures were a serious threat to the quality of raw milk.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms belonging to the phylum of Proteobacteria such as Acinetobacter (family Moraxellaceae) and Pseudomonas (family Pseudomonaceae) characterize Ctrl and GP+ cheeses after 2 days of ripening. Acinetobacter is a Gram-negative, psychrotrophic bacteria, that colonize teat canal and has been found in feces samples and as contaminant of raw milk [35]. Pseudomonas is the most important psychrotrophic bacteria in raw milk, coming from natural environment [36] and has been related to hygiene conditions [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Non-compliance with the hygiene standards of its acquisition makes it difficult to avoid the contamination of milk with microorganisms [2]. The level of microbiological contamination of milk depends on several factors such as animal health, farm sanitary conditions, milking hygiene, and milk storage temperature [3,4]. In most cases, unless the animal is suffering from a mammary gland infection or systemic disease, the milk produced by a mammary gland should not contain bacteria, although it is easily contaminated with microbes living on the animal's skin during milking.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant microbiota of chilled raw milk is psychrotrophic bacteria, capable of producing undesirable proteolytic and lipolytic enzymes, causing adverse changes in dairy products [3,4,8]. Among the most significant bacteria causing spoilage of dairy products are bacteria belonging to the genus of psychrotrophic Bacillus.…”
Section: Introductionmentioning
confidence: 99%